Fruit Bats are not Pests - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Farmers who slaughter fruit bats as pests may suffer losses in production greater than those caused by bats, because bats that feed on fruit and nectar have a crucial role in pollinating and dispersing the seeds of more than 500 species of plants...